Evaluasi Kinerja Jaringan DMVPN Menggunakan Routing Protocol RIPv2, OSPF, EIGRP dengan BGP - Arini Arini (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
Data communication has become a major requirement for companies and governmental institutions. Communication is not only limited to one particular local area but covers other areas so as to form a wide network (WAN). By using 3-phase DMVPN (Dynamic Multipoint Virtual Private Network) technology, government companies and institutions can communicate securely through the Internet network at lower cost and easier in configuration than similar solutions such as X.25, Frame Relay and ATM. In maximizing the performance of DMVPN required good network management, one of them by using a combination of internal and external routing protocol. In this study the routing protocol used RIPv2, OSPF, EIGRP and BGP with different algorithms, to compare them used QoS criteria (throughput, jitter, packet loss, network covergence). Methods of data collection with literature study and literature study, simulation done with 8 stages (problem formulation, conceptual model, input & output data, modeling, simulation, verification & validation, experimentation, and output analysis). The results of this study provide the best QoS value in phase 1 is EIGRP-BGP, phase 2 is EIGRP-BGP, and phase 3 is RIPv2-BGP. And EIGRP-BGP is the best combination of routing protocols for DMVPN.